Religious and psychological compatibility and its effect in shaping the personality of Muslim from da’wah perspective: A study in Sabha, Libya / Fatma Mohamed A W Ramdan - Fatma Mohamed , A W Ramdan (2018)
The study talks about religious and psychological compatibility in the refinement of the Muslim personality and shows the role of the preachers in their refinement, This study has four objective 1:- Analysis and statement of the truth of the soul in Islam and psychologists; to achieve comprehensive mental health, which reaches the human balance to make it successful at the family level and in work, and relations with others 2:- Diagnosis of self-evaluation and analysis of positive and negative characteristics And uncontrolled, And to clarify their impact on the self; to reach a balanced personality free of disturbances contrary to compatibility 3:- highlight the characteristics of the preacher and his influential ways in the refinement of ethics and the creation of psychological stabilit :- 4 realize that psychological and mental diseases have an impact on the Muslim personality, and to highlight the role of psychotherapist and Muslim preacher in reducing their impact,As well as the statement of the influence of worship in the compatibility and psychological confirmation. The study followed the analytical approach and the applied approach to interviewing a sample of professors of psychology and Islamic studies At the University of Sabha, as well as the distribution of questionnaire on a sample includes professors of psychology and preachers and others the study summar :- These are the theories used by psychologists to find psychological compatibility A clear simulation of the methods used by the Muslim preacher in refining the personality of the Muslim Which reveals the importance of religious consensus in the construction and stability of the Muslim personality and the common role between the Muslim and the psychological therapist to find a balanced personality, Is the interest in directing people to control their emotions and control in accordance with specific rules and controls, both according to its competence,The combination of these skills is possible for the Muslim preacher who has an advanced scientific rank In the field of forensic science.